2020
DOI: 10.1136/jitc-2019-000453
|View full text |Cite
|
Sign up to set email alerts
|

Phase IA/IB study of single-agent tislelizumab, an investigational anti-PD-1 antibody, in solid tumors

Abstract: BackgroundThe programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) axis plays a central role in suppressing antitumor immunity; axis dysregulation can be used by cancer cells to evade the immune system. Tislelizumab, an investigational monoclonal antibody with high affinity and binding specificity for PD-1, was engineered to minimize binding to FcγR on macrophages to limit antibody-dependent phagocytosis, a potential mechanism of resistance to anti-PD-1 therapy. The aim of this phase IA/IB study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 19 publications
7
134
0
Order By: Relevance
“…Time-varying clearance was not observed; clearance and volume of distribution of the central compartment were estimated as 0.164 L/day and 2.92 L, respectively [39]. The estimated terminal half-life of tislelizumab 200 mg Q3W was 16.8 ± 5.5 days [40]. Covariate analysis of population pharmacokinetics indicated that dose adjustments were not needed based on age, sex, race, body weight, tumor size, serum albumin level, or immunogenicity status [39].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 88%
See 3 more Smart Citations
“…Time-varying clearance was not observed; clearance and volume of distribution of the central compartment were estimated as 0.164 L/day and 2.92 L, respectively [39]. The estimated terminal half-life of tislelizumab 200 mg Q3W was 16.8 ± 5.5 days [40]. Covariate analysis of population pharmacokinetics indicated that dose adjustments were not needed based on age, sex, race, body weight, tumor size, serum albumin level, or immunogenicity status [39].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 88%
“…Of the 49 evaluable patients with NSCLC treated with tislelizumab 200 mg Q3W in the phase 1B dose-expansion phase, an objective response rate of 12.2% (95% CI: 4.6, 24.8) was observed, despite a high proportion of patients having received prior systemic drug therapy (n = 44, 90%) [40,41]. Clinical benefit was observed in both Asian and non-Asian patients [40], as well in patients with PD-L1-positive (≥25% of tumor cells exhibiting PD-L1 membrane) staining and PD-L1-negative (<25% PD-L1 tumor cell expression) tumors [41]. Across all patients from an openlabel phase 1/2 study conducted in China (BGB-A317-102; NCT04068519), treatment with tislelizumab resulted in a median overall survival of 11.5 months (95% CI: 9.1, 15.0) with a median follow-up of 12.2 months [42].…”
Section: Clinical Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Bear in mind that these phenotypes of SARS-CoV-2 infection might be frequent complications of other diseases and treatments. For example, dyspnea is a frequent complication of chronic respiratory diseases [46], lung cancer [47], and hepatopulmonary syndrome [48]; septic shock is a complication of pneumococcal pneumonia, chronic corticosteroid treatment, and current tobacco smoking [49]; fatigue is a complication of multi-type cancers [50,51] and Parkinson's disease [52]; and lymphopenia is a complication of human immunodeficiency viral infection [53].…”
Section: Database Contentmentioning
confidence: 99%